The Effect of Work Environment, Organizational Commitment, and Leadership on Lecturer Performance - Raju Gobal; Faudunasokhi Telaumbanua; Dadang Syaputra (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to analyze the effects of the work environment, organizational commitment, and leadership on lecturers' performance at Politeknik Negeri Media Kreatif PSDKU Medan. Lecturer performance is an important factor in improving the quality of higher education and enhancing institutional competitiveness. Research Method: This study employed a quantitative approach with an associative research design. The population consisted of 35 lecturers, and a saturated sampling technique was used. Data were collected through questionnaires using a Likert scale. Data analysis was conducted using SPSS, including validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, t-test, F-test, and coefficient of determination (R²). Results and Discussion: The study indicates that the work environment has a positive but insignificant effect on lecturers' performance. Organizational commitment has a positive and significant effect and is the most dominant variable. Meanwhile, leadership has a negative and insignificant effect on lecturer performance. Simultaneously, these three variables have a significant effect on lecturer performance. Implications: The findings of this study provide implications for higher education institutions to strengthen organizational commitment, improve the quality of the work environment, and develop more adaptive leadership practices. Originality: This study provides an empirical contribution by integrating the variables of work environment, organizational commitment, and leadership into a single research model within vocational higher education institutions.